Power Quality Improvement in Distribution System Using Parallel DSTATCOM - Alzubaidi, Ahmed Mohammed Mohsin; Rao, P. V. Ramana (International Journal of Engineering and Technology, 2018)
DSTATCOM is one among FACTS controllers to reduce harmonic effect in power system. Presence of non-linear loads induces harmonics to source components which in-turn affects other sensitive loads. Parallel custom devices share the compensating currents and as a result stress on individual custom device reduces. This paper presents power quality improvement using parallel DSTATCOM in power distribution system. The parallel DSTATCOM are controlled with a common single control scheme using synchronous reference frame theory. Proposed concept was implemented with MATLAB/SIMULINK software and results were discussed considering different loading conditions of the proposed system like balanced case non-linear load and unbalanced case non-linear load conditions.